Quality-of-life among women with breast cancer: application of the international classification of functioning, disability and health model - Al-Sharman, Alham; Al-Sarhan, Areen; Aburub, Ala; Shorman, Raid; Bani-Ahmad, Ali; Siengsukon, Catherine; Bani Issa, Wegdan; Abdelrahim, Dana N.; Hijazi, Heba; Khalil, Hanan (Frontiers in Psychology, 2024)
Background This study aimed to identify the factors that influence Breast Cancer (BC) women’s quality of life (QoL) based on the International Classification of Functioning, Disability and Health (ICF) framework. Method A cross-sectional study was conducted among 188 women with BC. The dependent variable, QoL, was measured using the Quality of Life Index (QLI-c). The independent variables were measured using the following Arabic-validated questionnaires: Pittsburgh Sleep Quality Index (PSQI), Female Sexual Function Index (FSFI), Modified Fatigue Impact Scale (MFIS), Hospital Anxiety and Depression Scale (HADS), and the International Physical Activity Questionnaire (IPAQ). Results There was a significant positive correlation between monthly income (r = 0.17, p = 0.016) and QoL, and significant negative correlation between the stage of disease (r = −0.221, p = 0.002) and duration of first diagnosis (r = −0.280, p = 0.004) with QoL. Poor sleep quality, sexual dysfunction, fatigue, depression, and anxiety had significant negative correlations with QoL (p < 0.01). Multiple regression analysis revealed that among the various factors that might affect QoL, sexual dysfunction, poor sleep quality, depression, and anxiety were significant predictors of QoL (p ≤ 0.05). Conclusion The ICF provided an excellent framework to explore the factors influencing QoL among women with BC. This study has given evidence for the relationship of demographic, clinical, and body functional factors with QoL among women with BC. Interestingly, sexual dysfunction, poor sleep quality, depression, and anxiety factors are predictors of QoL. Awareness of these factors that predict QoL will guide healthcare professionals to improve the health and QoL of BC women.